Comparison of Different Twin Row and Narrow Row Sowing Methods in Corn A Clay-Textured Soil - Betül Kolay; Özlem Avşar; Uğur Bilge; Kudret Berekatoğlu; Sevda Kılınç; Ferhat Oğurlu; Şehmus Atakul; Yener Çelik; Abdullah Eren; Ali Rıza Öztürkmen (Turkish Journal of Agriculture: Food Science and Technology)
Narrow and twin row sowing methods are agronomic applications that aim to increase plant growth and yield by expanding the plant's growing area but, they are highly affected by environmental conditions. The aim of this study is to determine the applicability of different narrow row and twin row sowing methods in clay textured soil in main crop cultivation of corn, which an important grain. The study was carried out Diyarbakır province in the Southeastern Anatolia Region of Türkiye in 2016 and 2017. In the study carried out with two different corn varieties, line abreast narrow row, diagonal narrow row, line abreast twin row, diagonal twin row, single row 1 (70 cm row spacing, 20 cm intra-row spacing) and single row 2 (70 cm row spacing, 12.5 cm intra-row spacing) applications were tried. ADA 351 and Sakarya corn varieties were used in the study. As a result it was determined that line abreast narrow row, diagonal narrow row, line abreast twin row and diagonal twin row applications are not suitable for corn cultivation. The highest grain yield was obtained from single row and 12.5 cm intra-row spacing application.